Pengaruh Edukasi Media Whatsapp Tentang Gizi Laktasi, Involusi Uteri, Dan Lochea Terhadap Pengetahuan, Sikap Dan Perilaku Ibu Nifas - Ratnaeni; Agussalim Bukhari; Healthy Hidayanty; Nurpudji Astuti Daud; Burhanuddin Bahar; Ni Luh Puti Herli Mastuti (Oksitosin : Jurnal Ilmiah Kebidanan, 2021)
The abnormal period of nifas causes problems such as the sub-involution of utero and bleeding, when it is not handled quickly can result in maternal mortality. Education is one of the upbringing to improve the knowledge, attitudes and behaviors of mother Nifas. The aim of this research is to know the effect of WhatsApp education on lactation, uteri, and Lochea on the knowledge, attitudes and behavior of puerperium in the working area of Sitti Khadijah I Muhammadiyah Makassar ". Research design that is quasi experiment with one group pre-Test and post-Test design. The research was conducted in Rsia Sitti Khadijah I Muhammadiyah Makassar in January S/d february year 2020. Sample of 39 respondents. Sampling technique using purposive sampling, intervention is given through WhatsApp media about lactation, utero and Lochea for 14 days with 2 times the provision of materials in a day and completed the division of the research material conducting group monitoring if the material is accessed then the name of the respondent is in the field "read by" but if it has not been accessed the name of the respondent is in the field Data was analyzed using Mc Nemar test. Result: Most of the respondents were 20-35 years old as much as 84.6%, the majority of the education of respondents was the college as much as 41.0%, respondents MOSTLY worked as IRT, which was 56.4%, most of the family income was 3-5 million per month as many as 69.2% and most respondents had a total of 2-4 children as much as 43.6%. There was a significant increase in the knowledge of 84.6% and an attitude of 79.5% after the intervention with P-value 0.000. While on the behavioral consumption of proteins, Vit A and vit C respectively at 35.9%, 41% and 59% after administration of the intervention with P value < 0.05. There is an increase in the knowledge, attitudes and behaviors of puerperium mothers in the work area of RSIA Sitti Khadijah I Muhammadiyah Branch of Makassar. And expected to be Pregnant and mother Nifas to make use of social media owned especially Whatsapp and Dipleaseto further researchers in order to develop this research using other social media. Keywords: Education, Social Media Whatsapp, Nutrition, Puerperium The abnormal period of nifas causes problems such as the sub-involution of utero and bleeding, when it is not handled quickly can result in maternal mortality. Education is one of the upbringing to improve the knowledge, attitudes and behaviors of mother Nifas. The aim of this research is to know the effect of WhatsApp education on lactation, uteri, and Lochea on the knowledge, attitudes and behavior of puerperium in the working area of Sitti Khadijah I Muhammadiyah Makassar ". Research design that is quasi experiment with one group pre-Test and post-Test design. The research was conducted in Rsia Sitti Khadijah I Muhammadiyah Makassar in January S/d february year 2020. Sample of 39 respondents. Sampling technique using purposive sampling, intervention is given through WhatsApp media about lactation, utero and Lochea for 14 days with 2 times the provision of materials in a day and completed the division of the research material conducting group monitoring if the material is accessed then the name of the respondent is in the field "read by" but if it has not been accessed the name of the respondent is in the field Data was analyzed using Mc Nemar test. Result: Most of the respondents were 20-35 years old as much as 84.6%, the majority of the education of respondents was the college as much as 41.0%, respondents MOSTLY worked as IRT, which was 56.4%, most of the family income was 3-5 million per month as many as 69.2% and most respondents had a total of 2-4 children as much as 43.6%. There was a significant increase in the knowledge of 84.6% and an attitude of 79.5% after the intervention with P-value 0.000. While on the behavioral consumption of proteins, Vit A and vit C respectively at 35.9%, 41% and 59% after administration of the intervention with P value < 0.05. There is an increase in the knowledge, attitudes and behaviors of puerperium mothers in the work area of RSIA Sitti Khadijah I Muhammadiyah Branch of Makassar. And expected to be Pregnant and mother Nifas to make use of social media owned especially Whatsapp and Dipleaseto further researchers in order to develop this research using other social media. Keywords: Education, Social Media Whatsapp, Nutrition, Puerperium ABSTRAK Masa nifas yang abnormal menyebabkan masalah seperti sub-involusi uteri dan perdarahan, apabila tidak tertangani dengan cepat dapat berakibat pada kematian ibu. Edukasi merupakan salah satu asuhan untuk meningkatkan pengetahuan, sikap dan perilaku ibu nifas. Tujuan penelitian ini adalah untuk Mengetahui efek edukasi whatsapp tentang gizi laktasi, involusi uteri, dan lochea terhadap pengetahuan, sikap dan perilaku ibu nifas di wilayah kerja RSIA Sitti Khadijah I Muhammadiyah Makassar”. Desain Penelitian yaitu quasi experiment dengan one group pre-test dan post-test design. Penelitian dilaksanakan di RSIA Sitti Khadijah I Muhammadiyah Makassar pada bulan Januari s/d Februari tahun 2020. Sampel sebanyak 39 responden. Tekhnik pengambilan sampel menggunakan purposive sampling, intervensi diberikan melalui media whatsapp tentang gizi laktasi, involusi uteri dan lochea selama 14 hari dengan 2 kali pemberian materi dalam sehari dan selesai pembagian materi peneliti melakukan pemantauan group jika materi telah diakses maka nama responden berada pada kolom “Dibaca Oleh” namun jika belum diakses nama responden berada pada kolom “Tersampaikan Ke”. Data dianalisis menggunakan uji Mc Nemar. Sebagian besar responden berumur 20-35 tahun yaitu sebanyak 84.6%, mayoritas pendidikan responden yaitu perguruan tinggi sebanyak 41.0%, responden sebagian besar bekerja sebagai IRT yaitu sebanyak 56.4%, Sebagian besar responden pendapatan keluarganya 3-5 juta perbulan sebanyak 69.2% dan sebagian besar responden memiliki jumlah anak 2-4 yaitu sebanyak 43.6%. Terjadi peningkatan yang signifikan terhadap pengetahuan sebesar 84.6% dan sikap sebesar 79.5% setelah pemberian intervensi dengan p-value 0.000. sedangkan pada perilaku konsumsi protein, VIT A dan VIT C masing-masing sebesar 35.9%, 41% dan 59% setelah pemberian intervensi dengan p value < 0.05. Terdapat peningkatan pengetahuan, sikap dan perilaku ibu nifas di wilayah kerja RSIA Sitti Khadijah I Cabang Muhammadiyah Makassar. Dan diharapkan ibu hamil maupun ibu nifas agar memanfaatkan media sosial yang dimiliki khususnya Whatsapp serta diharapkan peneliti selanjutnya agar bisa mengembangkan penelitian ini dengan menggunakan media sosial yang lainnya. Kata Kunci : Edukasi, Media Sosial Whatsapp, Gizi, Ibu Nifas